Germany—No Country for Old Workers? - Martin Dietz; Ulrich Walwei (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2011)
The employment situation of older workers in Germany used to be poor. However, in recent years it has improved considerably. Germany has shifted its policies to strengthen the labor market performance of older workers. Policy has focused on less early exits of older workers and far-reaching institutional changes concerning public pension schemes and unemployment benefit systems. A better overall development of the labor market and an increased labor force participation of women contributed to the more favorable employment situation of older workers. Nevertheless, we still observe severe problems for certain groups of older workers. The older workers are and the lower their skill level is the weaker is their labor market integration. If older persons are already unemployed they will experience severe difficulties to (re-)enter the labor market. In order to become actually a country for old workers the issue of employability needs much more attention. Such a strategy relies on continuous skill improvement as well as a healthy environment and does not only address older workers but also younger workers facing a prolonged working life.
Keywords: 330; ältere Arbeitnehmer; Beschäftigungsentwicklung; Arbeitsmarktpolitik; Erwerbsbeteiligung; altersspezifische Faktoren; Arbeitslose; Arbeitsmarktchancen; Beschäftigungsfähigkeit; lebenslanges Lernen; Altern; arbeitsmarktpolitische Maßnahme; Entgeltsicherung; Eingliederungszuschuss; Arbeitslosenquote; Erwerbsquote; Rente mit 67